Stable Isotopes of Ice on the Surface of Taylor Glacier, Antarctica - Cuffey, Kurt M.; Bliss, Andrew; Kavanaugh, Jeffrey; Aciego, Sarah (IEDA: US Antarctic Program Data Center, 2007)
Abstract: This data set contains Oxygen and Deuterium isotope ratios for approximately 980 sites on the surface of the ablation zone of Taylor Glacier, Antarctica. The data set gives latitude and longitude of collection, oxygen ratio (18/16) in per mil, and Deuterium ratio (H/D) in per mil. Data are in space-delimited ASCII text format and are available via FTP.